Strategi Pengembangan Camping Ground Desa Wonosalam Dusun Mangirejo dalam Perekonomian Pariwisata (International Forum of Researchers and Lecturers, 2023)
Tourism has a goal of helping the country's economy. Therefore it is necessary to develop tourism that can help local people by creating jobs and increasing regional income. Tourism development can be carried out in areas that have tourism potential, such as in Wonosalam Village, Wonosalam District, Jombang Regency. One of them is the Kebon Kopi tourist attraction located in Sumber Gogor, Mangirejo Hamlet, Wonosalam Village, where there is a program to develop coffee gardens as camping ground locations to increase its natural tourism potential. The research method uses qualitative methods with data collection techniques through observation, interviews and literature review. The results of the discussion show that the development of the camping ground in Wonosalam Village, Dusun Mangirejo requires a coffee plantation development strategy with the concept of attracting tourists or visitors and opening up the tourism economy.